Covid-19: Organizações questionam gastos do Governo moçambicano | DW | 11.08.2020 - Deutsche Welle (DW.COM, 2020)
Em Moçambique, a sociedade civil aponta falta de transparência e pede esclarecimentos ao Governo sobre os 14 mil contratos sem concurso público e os 68 mil milhões de meticais gastos durante o estado de emergência.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; accountability / responsabilização; health - COVID-19 / saúde – COVID-19; health / saúde; transparency / transparência

Unpacking the Potential Socioeconomic Impact of the Coronavirus Pandemic in Mozambique: A United Nations Situation Analysis and Policy Recommendations - United Nations Mozambique (United Nations, 2020)
The Coronavirus pandemic arrives in Mozambique at a time when, after several years of modest economic performance, the Mozambican economy was starting to show signs of recovery. Hence, the latest projections of the IMF of November 2019 had the Mozambican economy growing at 6% in 2020, with medium term projections reaching 9% and above after 2023, following the initiation of LNG exploration operations in the north of the country. Despite this improving macroeconomic outlook prior to the outbreak of the Coronavirus pandemic, living conditions for many Mozambicans remain harsh. Poverty afflicts almost half of the population, 46.1% according to the 2014/15 national household survey, and many people continue without access to basic services, with the proportion of Mozambicans with access to basic water supply, basic sanitation and electricity remaining at very low levels: 55.7%, 29.4% and 27.4% in 2017, respectively. Moreover, despite improvements in healthcare conditions, Mozambicans, especially women and children, continue to be severely afflicted by disease and sickness. In general, living conditions tend to be worse in rural than in urban parts of the country. The coronavirus pandemic is almost certainly going to change this short- and medium-term economic outlook and could potentially have a very significant socioeconomic impact in Mozambique. However, while all available evidence points in this direction, at this stage it is difficult to ascertain and quantify the extent of this impact, given the speed at which things are changing around the world and the uncertainly surrounding the epidemiological profile of the Coronavirus, which makes it hard to assess how long the containment and lockdown measures being applied around the world will need to remain in place. While a detailed quantification of the socioeconomic impact of the coronavirus pandemic may not be feasible, it is still useful to identify possible transmission channels through which the pandemic may affect the Mozambican economy and society. It is also useful to identify key issues that are likely shape shortand medium-term socioeconomic prospects in Mozambique as a result of the Coronavirus pandemic outbreak in Mozambique. The following sections outline some of these.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico; health - COVID-19 / saúde – COVID-19; health / saúde

A segurança social em Moçambique: conversa para o boi dormir ou um instrumento de redistribuição viável? - Castel-Branco, Ruth Kélia (Desafios para Moçambique 2020, 2020)
Nas últimas décadas, houve uma ressurgência de interesse na Segurança Social como instrumento redistributivo capaz de reduzir a pobreza e a desigualdade e promover o crescimento económico inclusivo. Este crescente interesse a nível global deve-se ao reconhecimento de que o desenvolvimento social não resulta inevitavelmente do crescimento económico, e, aliás, pode ser bem o contrário: que formas de Segurança Social vinculadas ao emprego formal são inadequadas dada a informalidade generalizada e que transferências monetárias não contributivas são possíveis mesmo em países em vias desenvolvimento como Moçambique (Mkandawire, 2011). Nas duas décadas anteriores à crise da Ematum, Moçambique registou um índice de crescimento médio de 7,5 % do PIB. Porém, impulsionado por uma indústria extractiva intensiva em capital, este não resultou em melhores condições de vida para a maioria dos moçambicanos. A Crise da Ematum piorou a situação. Segundo simulações da UNU-WIDER, a crise resultou no aumento do índice da pobreza de 46,1 % em 2014, e de aproximadamente 60 % em 2016 (Mambo et al., 2018). Alarmado pela situação, o antigo Ministro de Administração Estatal, Óscar Monteiro, sugeriu, durante a reunião do Comité Central da Frelimo em Maio de 2019, a rápida expansão do sistema de Segurança Social em Moçambique, mas o Governo optou por não a fazer: "A gravidade da situação requer medidas urgentes. E eu digo isto não porque não é apenas uma questão eleitoral, mas é uma questão de humanidade... Porque é que nós não começamos a distribuir dinheiro, usando a rede existente, ampliando, melhorando... Esse dinheiro não se vai perder... Esse dinheiro vai aumentar o consumo, vai encorajar a produção, vai financiar a recuperação. (Monteiro, 2019)" A crise da Covid expôs mais uma vez a fragilidade do nosso modelo de desenvolvimento económico, e a fraqueza dos mecanismos de redistribuição existentes. Projecções da UNU-WIDER concluíram que apenas 7 % dos moçambicanos tinham as condições para sobreviver a um lockdown total (Jones, Egger & Santos, 2020). O Governo acabou por optar por um lockdown parcial, permitindo que várias instituições públicas e privadas continuassem abertas. No entanto, a questão da expansão da Segurança Social continua oportuna não só como medida de resposta de emergência durante a crise da Covid, mas também como instrumento redistributivo com a capacidade de promover o desenvolvimento inclusivo. Este artigo começa por uma análise do actual sistema de Segurança Social, seguida por uma discussão das medidas de emergência que foram propostas, as sugestões rumo a um sistema de Segurança Social universal, e os riscos – principalmente o risco da financeirização da Segurança Social com a terceirização dos sistemas de registo e pagamentos. O artigo é concluído com uma discussão do tipo de mobilização que será necessário para garantir a expansão adequada da Segurança Social. Como disse o abolicionista Frederick Douglass, «sem luta não há progresso... O poder não concede nada sem demanda. Nunca concedeu e nunca concederá» (Frederick, 1851).
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; Social security / segurança social; health - COVID-19 / saúde – COVID-19; social protection / proteção social

Pânico e Medo: Desafios Dos Media Moçambicanos na Cobertura da COVID-19 - Joanguete, Celestino (Desafios para Moçambique 2020, 2020)
O principal foco do estudo são os diferentes enquadramentos da tonalidade discursiva adoptada pelos media nas suas narrativas sobre o novo coronavírus. Nesta perspectiva, a principal concentração como objecto de estudo são a rádio, a televisão, o jornal e as redes sociais da Internet. Neste último medium, escolhemos analisar especificamente as narrativas do Facebook e WhatsApp por serem as redes sociais mais populares em Moçambique. Socorremo-nos de duas metodologias de estudo bastante presentes no campo das ciências sociais, a análise de conteúdo desenvolvida por Bardin (2006) e a de observação sistemática. Foi fundamental adoptar estes métodos pela vantagem de permitirem recolher dados no momento da ocorrência dos factos, sem criar situações artificiais, e avaliar alguns aspectos para os quais não há outras técnicas de recolha de evidências. Uma análise sobre os diversos atributos descritivos do coronavírus permitiu compreender a construção do discurso mediático e a sua influência social. A análise de conteúdo das narrativas dos media moçambicanos facilitou a compreensão dos elementos constitutivos de textos jornalísticos, nas produções discursivas dos quais os termos, os adjectivos, as imagens, as descrições, o foco e as temáticas desempenham o papel fundamental.
Keywords: *indexed; G - Mozambique / Moçambique; L - portuguese / português; health - COVID-19 / saúde – COVID-19; health / saúde

Democracy Index 2020 In sickness and in health? - The Economist Intelligence Unit (The Economist, 2020)
The main focus of the report is the impact of the coronavirus (Covid-19) pandemic on democracy and freedom around the world. It looks at how the pandemic resulted in the withdrawal of civil liberties on a massive scale and fuelled an existing trend of intolerance and censorship of dissenting opinion (see page 14). The report also examines the state of US democracy after a tumultuous year dominated by the coronavirus pandemic, the Black Lives Matter movement and a hotly contested presidential election (see page 42). The results by region are analysed in greater detail in the section entitled “Democracy around the regions in 2020” (see page 26).
Keywords: *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; civil society / sociedade civil; health - COVID-19 / saúde – COVID-19

Mozambique Annual Report 2020: Responding to a Year of Crisis - Wojnar, Andrea M; Lomelin, Jessica; Baker, Daniel; Salu, Karlina; Macangira, Assane; Manjate, Epidauro (UNFPA, 2020)
In the case of Mozambique, the pandemic came on the heels of two destructive cyclones that had devastated large parts of the country in 2019 and whose consequences were still being felt. In northern Mozambique, increasing violence in Cabo Delgado province resulted in a surge of internally displaced persons into local communities in Cabo Delgado, Nampula and Niassa provinces. With host communities ill equipped to meet the needs of those displaced, this population movement created a new humanitarian crisis in the midst of the pandemic. Like all of our governmental, civil society and donor partners, the resilience of UNFPA was tested, and we had to adjust quickly after the first case of COVID-19 was confirmed in March and the Government declared a state of emergency. At the most basic level, women continued to get pregnant and babies were still being born, even in the middle of a pandemic. Addressing the needs of adolescent girls and young women could not be put on hold. Helping to meet the needs of the symbolic target of UNFPA’s work – “the 10-year-old girl” – could not wait until she was 11. Helping to meet her aspirations for the future, advocating and working for her growth and self-fulfillment as a woman leading a healthy, productive and violence-free life – these could not wait a year.
Keywords: G - Mozambique / Moçambique; Health PEA; L - english / inglês; gender / género; health - COVID-19 / saúde – COVID-19; health / saúde; youth / juventude